PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. SUMBER ALFARIA TRIJAYA, TBK PALEMBANG - Teguh Santoso; Yunidar Erlina; Yancik Syafitri; Ernawati Ernawati; Ellen Sumiarni (Institut Rahmaniyah Sekayu, 2023)
This research was conducted to determine how much influence the transformational leadership style, compensation and work environment have on employee job satisfaction at PT. Sumber Alfaria Trijaya, Tbk Palembang. The sample in this study were employees of PT. Sumber Alfaria Trijaya, Tbk Palembang which is taken using the slovin formula. So the sample size in this study was 72 respondents from the employee population of PT. Sumber Alfaria Trijaya, Tbk. Palembang which will be the respondent. The analytical method used is multiple linear regression analysis by comparing the four research variables. Based on simultaneous hypothesis testing (statistical F test) with a significance value of 0.00 <0.05 which indicates that there is a simultaneous significant effect of the variable transformational leadership style, compensation and work environment on employee job satisfaction and with the test value of the coefficient of determination the results obtained that simultaneously or simultaneously the three independent variables namely transformational leadership style, compensation and work environment are able to explain changes in job satisfaction variables of 25.8% and the other 74.2% are influenced by other variables not included in this regression model.